The anomalous luminescent behaviors of the Nd3+/Yb3+ co-doped yttrium silicate at different physical conditions - Cinkaya, Hatun; Eryurek, Gonul; Di Bartolo, Baldassare (IOP Publishing, 2019)
We performed the luminescence measurements in 1% Nd3+/10% Yb3+ co-doped yttrium silicate (Y2O3:SiO2) nanopowder at atmospheric pressure and a vacuum (0.01 mbar) with the near-infrared (808 nm) laser diode excitation. The sample was synthesized by sol-gel method and annealed at 1250 degrees C for 12 h. The emission was observed with the wide bands corresponding to the energy transitions of Nd3+ ions and the energy transfer between Nd3+ and Yb3+ at various excitation power densities. The emitted light intensity was not stable at atmospheric pressure while it was more stable at 0.01 mbar. It was seen that the thermal effects due to the laser absorption, duration of the measurement and also focusing arrangements play a more important role in the luminescence behavior at atmospheric pressure. We report the anomalous 's'-shape pump power dependency of the up-converted green and red emissions obtained under vacuum (0.01 mbar). We have also investigated the luminescence dynamics of these emissions by analyzing the rise and decay patterns. The threshold power to obtain very bright white light was decreased under vacuum condition and the color quality parameters were also analyzed for all the experimental conditions.